Do Early Active Labor Market Policies Improve Outcomes of Not-Yet-Unemployed Workers? Findings from a Randomized Field Experiment - Gerard J. van den Berg; Gesine Stephan; Arne Uhlendorff (Institute of Labor Economics (IZA), 2025)
Inequality is a dynamic phenomenon, and the relative and absolute positions of individuals are subject to frequent shocks. It is important to know if preventive interventions mitigate adverse inequality effects of labor market shocks. We consider individuals up to three months before the envisaged termination of their employment and we study effects of pre-unemployment participation in active labor market programs (ALMP) on labor market outcomes using a randomized controlled trial (RCT). This complements the vast literature on ALMP for unemployed workers. Policies include signing an integration agreement (IA), preparing an action plan (AP) before the first meeting with a caseworker, and the combination of both. Results suggest that the IA - particularly when combined with the AP - increases the probability of employment around 4 months after registration as soon-to-be unemployed. This is driven by workers with a relatively high unemployment risk following registration. Thus, the policies contribute to reducing societal inequality.
Keywords: J68; J64; C93; 330; inequality; unemployment; work; job-to-job transitions; integration agreements; action plans; randomized controlled trial; job search; monitoring; counseling; machine learning